1993
DOI: 10.1016/0378-4274(93)90062-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic changes in primary, immortalized and malignant mammalian cells

Abstract: SUMMARY 283Some chromosomes in transformed rat cells and somatic cell hybrids fail to display the presence of kinetochore proteins as detected by antikinetochore antibodies. Suchchromosomes (K-Chromosomes) may constitute a novel mechanism for the genesis of aneuploidy. Wehave analyzed primary~ immortalized and malignant marnmalian cells for the presence of kinetochore proteins and micronuclei. Our resuJts suggest a correlation of the K-chromosome and micronucleus frequency with the variability in chromosome nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…One could expect that this continuous cell line would give limited intra-and inter-laboratory variation in the number of spontaneous MN. However, there is a good correlation between the mean 406 spontaneous MN frequency in our studies and those obtained by Kirchner et al (1993); 4.5 Ϯ 2.4/2000 mononucleate cells (range 0-10 MN/2000 mononucleate cells) and 3.7 Ϯ 0.6/2000 mononucleate cells, respectively. This rate is lower than the baseline level observed in cultured human T lymphocytes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…One could expect that this continuous cell line would give limited intra-and inter-laboratory variation in the number of spontaneous MN. However, there is a good correlation between the mean 406 spontaneous MN frequency in our studies and those obtained by Kirchner et al (1993); 4.5 Ϯ 2.4/2000 mononucleate cells (range 0-10 MN/2000 mononucleate cells) and 3.7 Ϯ 0.6/2000 mononucleate cells, respectively. This rate is lower than the baseline level observed in cultured human T lymphocytes.…”
Section: Discussionsupporting
confidence: 80%
“…As a matter of fact, a recent evaluation of the MLA database by the Environmental Protection Agency's Gene-Tox Mouse Lymphoma Committee gave no support to Storer's contention that the assay gives positive results for a large number of non-carcinogens (Clark et al, 1998). These mouse lymphoma cells show several other advantages, such as: growth in suspension (no need for trypsinization), rapid growth (doubling time of~10-12 h), unsynchronized division, stable karyotype and low and reproducible incidence of spontaneous MN (Kirchner et al, 1993). One could expect that this continuous cell line would give limited intra-and inter-laboratory variation in the number of spontaneous MN.…”
Section: Discussionmentioning
confidence: 99%
“…If primary cultures of lymphocytes and fibroblasts are irradiated, mitotic nondisjunction becames the basic mechanism of aneuploidy [67]. In nondisjunction an extra chromosome remains in one of the daughter cells.…”
Section: Aneuploidymentioning
confidence: 99%
“…It has been discovered that accelerated decondensation of the chromatin of individual chromosomes in connection with a disturbance in the kinetochore organization is apparently also accompanied by aneuploidy [76]. Aneuploidy may by induced by changes in the length of the cell cycle, a disturbance in the synchronic-ity of cleavage of the centromeric regions of daughter chromosomes [67], and by nondisjunction of chromosomes [78]. (6) A change in the interaction between the centromeric regions of daughter chromatids in the process of mitosis.…”
Section: Aneuploidymentioning
confidence: 99%
“…In addition to SHE cells which we have previously used , we chose L5178Y mause cells because of their low incidence of spontaneaus micronuclei (Kirchner et al, 1992) and because we have previously shown that 5-azacytidine induces TFf resistance in these cells (McGregor et al, 1989). In this paper we report that approximately 80% of the 5-azacytidine induced micronuclei did not stain for kinetochores and for centromeric heterochromatic DNA suggesting that 5-azacytidine is primarily a clastogen.…”
mentioning
confidence: 99%